FTKKP shines at CITREX 2023 with outstanding innovations and research achievements - Azizul Helmi, Sofian; Rozaimi, Abu Samah; Nur Aminatulmimi, Ismail (2023)
Huge congratulations to all outstanding researchers and innovators from FTKKP for their exceptional performance at CITREX 2023! The event, which took place on 12-14 March 2023 at UMP Kampus Gambang, showcased the latest creations and technological advancements from the Malaysian academic and research community.